c-Src functionality controls self-renewal and glucose metabolism in MCF7 breast cancer stem cells. - Víctor Mayoral-Varo; Annarica Calcabrini; María Pilar Sánchez-Bailón; Óscar H Martínez-Costa; Cristina González-Páramos; Sergio Ciordia; David Hardisson; Juan J Aragón; Miguel Ángel Fernández-Moreno; Jorge Martín-Pérez (PLoS ONE)
Deregulation of Src kinases is associated with cancer. We previously showed that SrcDN conditional expression in MCF7 cells reduces tumorigenesis and causes tumor regression in mice. However, it remained unclear whether SrcDN affected breast cancer stem cell functionality or it reduced tumor mass. Here, we address this question by isolating an enriched population of Breast Cancer Stem Cells (BCSCs) from MCF7 cells with inducible expression of SrcDN. Induction of SrcDN inhibited self-renewal, and stem-cell marker expression (Nanog, Oct3-4, ALDH1, CD44). Quantitative proteomic analyses of mammospheres from MCF7-Tet-On-SrcDN cells (data are available via ProteomeXchange with identifier PXD017789, project DOI: 10.6019/PXD017789) and subsequent GSEA showed that SrcDN expression inhibited glycolysis. Indeed, induction of SrcDN inhibited expression and activity of hexokinase, pyruvate kinase and lactate dehydrogenase, resulting in diminished glucose consumption and lactate production, which restricted Warburg effect. Thus, c-Src functionality is important for breast cancer stem cell maintenance and renewal, and stem cell transcription factor expression, effects linked to glucose metabolism reduction.